Functional Evaluation of Acute Achilles Tendon Rupture Treatment Using the Dresden Technique: A Case Series - Fornino, Giovanni; Leme Godoy-Santos, Alexandre; Diniz Fernandes, Túlio; Sousa Macedo, Rodrigo; Lagus Rosemberg, Dov; Barban Sposeto, Rafael (Journal of the Foot & Ankle, 2026)
To evaluate functional outcomes, quality of life, and complications after repair of acute Achilles tendon rupture using a minimally invasive Dresden technique. Achilles rupture is common, and management remains debated; minimally invasive approaches aim to preserve functional outcomes while reducing soft-tissue complications and sural nerve injury risk. Single-center case series (2015–2024) at a tertiary orthopedic institute. Adults with noninsertional acute ruptures (≤2 weeks) underwent repair with the Dresden technique, using minor instrument modifications and a standardized rehabilitation protocol. Outcomes included Foot and Ankle Outcome Score (FAOS), Achilles Tendon Total Rupture Score (ATRS), EuroQol 5-Dimension 5-Level questionnaire (EQ-5D-5L), Patient Reported Outcomes Measurement Information System (PROMIS), heel-rise test, calf circumference, maximum plantarflexion/dorsiflexion, and gravitational equinus angle. Thirty-one patients (mean age 37.0 ± 10.55 years; 64.5% male) completed follow-up. Mean scores: FAOS 99.03 ± 1.73, ATRS 98.29 ± 2.64, EQ-5D-5L 0.98 ± 0.03, PROMIS 61.0 ± 0.51 (range 60.3–61.5). Heel-rise: 24/31 (77.4%) maintained single-leg support. Complications: none for infection, wound dehiscence, rerupture, or deep vein thrombosis; two transient sural nerve-related symptoms resolved by 2 months. Plantarflexion: 25.42° (operated) vs 25.45° (nonoperated), mean difference 0.03° (SD 0.18), p > 0.05. Dorsiflexion and gravitational equinus: no significant side-to-side differences. Calf circumference difference 1.08 cm (p < 0.05), not correlated with functional scores (p > 0.05). Very strong, statistically significant intercorrelations were observed among FAOS, ATRS, EQ-5D-5L, and PROMIS. The modified minimally invasive Dresden repair yielded excellent functional outcomes, high quality-of-life scores, and very low complication rates, with no meaningful deficits in ankle range of motion. Calf atrophy was small and not functionally relevant.